Analysis of tuberculosis infection in children with negative results of the test with a recombinant tuberculosis antigen - Юлия Яровая; Марина Лозовская; Елена Васильева; Людмила Клочкова; Анна Мосина; Геннадий Степанов (Academy of Sciences of Moldova, 2019)
Analiza infecției tuberculoase la copiii cu rezultate negative a testului cu antigen tuberculos recombinant